Implementation of School Physical Observations As a First Step for Education Students - Hamidiyah, Masita; Gani, Liyundzira Fikroh; Napitupulu, Maya Farhanna; Harahap, Zulkarnain; Siregar, Deasy Yunita (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
The use of physical school observation as a preliminary measure for education pupils is covered in this article. This school's setting is purposefully chosen to encourage the development of peaceful, suitable learning environments. The goal of MTsN 2 Medan, a renowned madrasah, is to create a populist, Islamic, high-quality, and ecologically sustainable MTsN 2 Medan. There are 32 pupils accessible in a single class at MTsN 2 Medan, out of the 95 teachers on staff. This school has enough infrastructure and facilities, both in terms of the kind of equipment, the proportions, and the general quality or state of the well-maintained facilities. Activities related to teaching and learning follow the guidelines of the Permendiknas-based educational units, specifically the use of learning implementation plans (RPPs). This study used an observational data gathering method with a qualitative descriptive research design. According to the study's findings, MTsN 2 Medan is a school with excellent facilities for both instruction and learning. The infrastructure offered is in line with what students require to learn. The curriculum is implemented using the guidelines set forth by Permendikbud. The standards of the learning process are also followed by the teaching and learning activities.